A new alcyonacean octocoral (Cnidaria, Anthozoa, Octocorallia) from Chilean fjords - Breedy Shadid, Odalisca (2015)
A new species, Swiftia comauensis, is described from Chile. It occurs in shallow waters from 18 to 59 m in the Patagonian fjord region and seems to be endemic to the northern part of the region. The species is characterized by having straggly colonies with sparse branching and long drooping branches, prominent polyp mounds, and long, thin spindles; the colonies are bright orange with pale yellow polyp mounds. A sharp decline in colony abundance was observed between 2003 and 2013, and in January 2014 a proposal was submitted to the IUCN for the addition of this taxon to the Red List of Threatened Species.